2013
DOI: 10.5402/2013/306595
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signaling and Cellular Pathways for Virus Entry

Abstract: The cell signaling plays a pivotal role in regulating cellular processes and is often manipulated by viruses as they rely on the functions offered by cells for their propagation. The first stage of their host life is to pass the genetic materials into the cell. Although some viruses can directly penetrate into cytosol, in fact, most virus entry into their host cells is through endocytosis. This machinery initiates with cell type specific cellular signaling pathways, and the signaling compounds can be proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…In previous work we showed that β1-integrin receptors, that normally mediate cell-cell and cell-ECM contact, play a role in the internalization of non-viral gene delivery vectors by MDCK cells 11 . Likewise, integrins are exploited by viruses to attach to and infect epithelial cells 19 20 . Izmailyan and colleagues found that vaccinia virus invasion through β1-integrin activates PI3K/Akt signaling 21 .…”
Section: Resultsmentioning
confidence: 99%
“…In previous work we showed that β1-integrin receptors, that normally mediate cell-cell and cell-ECM contact, play a role in the internalization of non-viral gene delivery vectors by MDCK cells 11 . Likewise, integrins are exploited by viruses to attach to and infect epithelial cells 19 20 . Izmailyan and colleagues found that vaccinia virus invasion through β1-integrin activates PI3K/Akt signaling 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Upon infection, Vaccinia virus enters the cell via micropinocytosis and becomes uncoated (Chi and Liu, 2012;Moss, 2012). Whereas the viral genome is silent in these initial events, all subsequent steps of the replication cycle are dependent on viral transcription and translation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, cellular signaling networks are required for replication, translation, nuclear membrane transport, capsid assembly, and dispersion, as well as the reactivation of virus latency to produce infectious virus (Chi and Liu 2013 ). On the other hand, the immune system is equipped with a sophisticated mechanism that can respond to a variety of infections (Klimpel 1996 ; Chaplin 2010 ).…”
Section: Hyper Inflammation and Cytokine Storm; Signaling Pathwaysmentioning
confidence: 99%